Diagnostic-test evaluation of immunoassays for anti-Toxoplasma gondii IgG antibodies in a random sample of Mexican population - Heriberto Caballero-Ortega; Rocío Castillo-Cruz; Sandra Murieta; Luz Belinda Ortíz-Alegría; Esther Calderón-Segura; Carlos J Conde-Glez; Irma Cañedo-Solares; Dolores Correa (Journal of Infection in Developing Countries)
Introduction: There are few articles on evaluation of Toxoplasma gondii serological tests. Besides, commercially available tests are not always useful and are expensive for studies in open population. The aim of this study was to evaluate in-house ELISA and western blot for IgG antibodies in a representative sample of people living in Mexico. Methodology: Three hundred and five serum samples were randomly selected from two national seroepidemiological survey banks; they were taken from men and women of all ages and from all areas of the country. ELISA cut-off was established using the mean plus three standard deviations of negative samples. Western blots were analysed by two experienced technicians and positivity was established according to the presence of at least three diagnostic bands. A commercial ELISA kit was used as a third test. Two reference standards were built up: one using concordant results of two assays leaving the evaluated test out and the other in which the evaluated test was included (IN) with at least two concordant results to define diagnosis. Results: the lowest values of diagnostic parameters were obtained with the OUT reference standards: in-house ELISA had 96.9% sensitivity, 62.1% specificity, 49.6% PPV, 98.1% NPV and 71.8% accuracy, while western blot presented 81.8%, 89.7%, 84.0%, 88.2% and 86.6% values and the best kappa coefficient (0.72-0.82). Conclusions: The in-house ELISA is useful for screening people of Mexico, due to its high sensitivity, while western blot may be used to confirm diagnosis. These techniques might prove useful in other Latin American countries.